2017
DOI: 10.1007/s00221-017-5127-9
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cervical movement on eye stabilization reflexes: a randomized trial

Abstract: To investigate the influence of the amount of cervical movement on the cervico-ocular reflex (COR) and vestibulo-ocular reflex (VOR) in healthy individuals. Eye stabilization reflexes, especially the COR, are changed in neck pain patients. In healthy humans, the strength of the VOR and the COR are inversely related. In a cross-over trial the amplitude of the COR and VOR (measured with a rotational chair with eye tracking device) and the active cervical range of motion (CROM) was measured in 20 healthy particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
(43 reference statements)
0
12
1
Order By: Relevance
“…This issue may be explained by the presence of dizziness could be mediated by an amplified central sensitization process (Holle et al, 2015) Recently, the cervico-ocular reflex was shown to be increased in both patients with chronic nontraumatic neck pain without dizziness and patients with chronic traumatic neck pain due to whiplash with associated dizziness. The role of reflexes should be compared in patients who suffer from NSCNP with or without associated dizziness for future studies (Ischebeck et al, 2018). In addition, a very relevant aspect in cervical dizziness which was not measured in the Manuscript to be reviewed present study is the cervical movement.…”
Section: Discussionmentioning
confidence: 98%
“…This issue may be explained by the presence of dizziness could be mediated by an amplified central sensitization process (Holle et al, 2015) Recently, the cervico-ocular reflex was shown to be increased in both patients with chronic nontraumatic neck pain without dizziness and patients with chronic traumatic neck pain due to whiplash with associated dizziness. The role of reflexes should be compared in patients who suffer from NSCNP with or without associated dizziness for future studies (Ischebeck et al, 2018). In addition, a very relevant aspect in cervical dizziness which was not measured in the Manuscript to be reviewed present study is the cervical movement.…”
Section: Discussionmentioning
confidence: 98%
“…The vestibular receptors of the inner ear are known to accurately detect movements of the head (Chin, 2018). The VOR receives input from the vestibular receptors, responding to movements of the head (Ischebeck et al, 2018). Electrical stimulation is a well-known procedure used to stimulate the vestibular system (Fitzpatrick and Day, 2004;Kim and Curthoys, 2004;Uchino and Kushiro, 2011;Yang et al, 2015;Fujimoto et al, 2016;Wuehr et al, 2016;Inukai et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the participant's head was passively turned approximately 5-15 • at 0.1-33 s for VOR assessment (Halmagyi et al, 2017;Ischebeck et al, 2017Ischebeck et al, , 2018. However, in daily living, when people actively turn their heads faster and wider and gaze at the fixation target, their eye movement can compensate for the head turn to maintain their gaze on FIGURE 1 | Experimental design for the eye-head coordination task.…”
Section: Recording Of Reflexive Eye Movementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the cervico-ocular reflex was shown to be increased in both patients with chronic non-traumatic neck pain without dizziness and patients with chronic traumatic neck pain due to whiplash with associated dizziness. The role of reflexes should be compared in patients who suffer from NSCNP with or without associated dizziness for future studies (Ischebeck et al, 2018). In addition, a very relevant aspect in cervical dizziness which was not measured in the present study is the cervical movement.…”
Section: Discussionmentioning
confidence: 99%